Fostering quantity surveying student success through academic engagement: an interactive qualitative analysis - Gerrit Crafford; Liezel Frick (Journal of Construction Project Management and Innovation)
This research paper delves into the multifaceted aspects influencing student engagement in higher education, specifically focusing on Bachelor of Science (Quantity Surveying) Honours (QS) students at Nelson Mandela University, South Africa.  This study aims to develop a group systems influence diagram (SID) for factors influencing student engagement according to QS students since it enhances student success and persistence.  The objectives are to identify the key factors that drive student engagement and understand their interrelationships.  This study used an interpretivist paradigm, which emphasises participants' subjective experiences, to navigate this complex landscape.  Methodologically, a blend of inductive and deductive approaches was employed for theory building.  The interactive qualitative analysis (IQA) strategy anchored this multi-method qualitative design.  Central to this approach was creating a student SID, a visual tool designed to map out and represent the myriad factors influencing student engagement.  Data collection was a two-pronged process, encompassing focus group discussions and subsequent individual interviews with students.  This strategy ensured a rich tapestry of insights, capturing both collective sentiments and individual narratives.  In response to the question, "Tell me about what influences your academic engagement at Nelson Mandela University?" the QS students produced 41 items in the focus group through inductive coding.  These items were grouped into seven themes by means of axial coding: physical environment, external realities, lecturer attributes, subject matter, teaching methods, personal factors, and student interaction.  Subsequently, a composite SID identified the physical environment and external realities themes as the primary drivers, while the lecturer attributes and subject matter themes were secondary drivers.  During phase two, the themes were verified through individual semi-structured interviews.  It was established that these  interviews substantiated the focus group findings.  The findings underscore the need for educational institutions to consider a holistic approach to student engagement, which includes creating conducive physical learning environments, understanding and addressing external challenges students face, and ensuring that teaching methods are engaging and adaptable.  Additionally, the study highlights the importance of lecturer attributes in shaping student engagement, suggesting targeted professional development and support for educators.  By tackling the drivers of student engagement, the Department of Quantity Surveying at Nelson Mandela University can foster an environment where students are more attentive, motivated, and actively involved in their learning experiences, ultimately leading to improved academic success.